Medullary thyroid cancer in MEN2 pediatric/adolescent carriers of RET mutation: genotype/phenotype correlation and outcome in a retrospective series of 23 patients - Di Benedetto, Guenda; Barca, Ignazio; De Gregorio, Laura; Scollo, Claudia; Gianì, Fiorenza; Martorana, Federica; Russo, Marco; Frasca, Francesco; Pellegriti, Gabriella; Sapuppo, Giulia (Frontiers in Oncology, 2025)
BackgroundMultiple endocrine neoplasia type 2 syndrome (MEN2) is a hereditary disease resulting from mutations of the rearranged during transfection (RET) protooncogene subclassified into MEN2A [medullary thyroid carcinoma (MTC), pheochromocytoma, and primary hyperparathyroidism] and MEN2B (MTC, pheochromocytoma, Marfanoid habitus, mucous neuromas, and intestinal ganglioneuromatosis). Prophylactic thyroidectomy is recommended in RET-mutated patients. The age at which it should be performed depends on the type and aggressiveness of the mutation.Aim of the studyThis study aimed to evaluate the genotype/phenotype correlation and outcome in pediatric/adolescent carriers of MEN2 RET mutation.Patients and methodsIn a retrospective series of 23 carriers of RET MEN2 mutation who were ≤19 years old at diagnosis and had undergone total thyroidectomy ± lymphadenectomy, the following were analyzed: 1) specific RET mutation, 2) clinical and histopathological characteristics, 3) genotype/phenotype correlation, and 4) outcome at last follow-up.ResultsIn our series, the female gender was more prevalent (F/M ratio 2.8/1), and the median age was 14.9 years [interquartile range (IQR) 12.6–17.2]. RET mutations were at very high risk in 4.3% of patients (M918T), high risk in 43.5% (C634), and moderate risk in 52.2% (47.8% C618 and 4.3% C620). All patients underwent surgery: at histology, MTC was found in 19/23 (82.6%) patients, C-cell hyperplasia in 2/23 (8.7%), and benign histology in 2/23 (8.7%). Ten patients (52.6%) had a disease event during the follow-up: 2/19 (10.5%) showed biochemical disease, 6/19 (31.6%) lymph node recurrences, and 2/19 (10.5%) distant metastases (50% liver, 50% bone). At the last follow-up, nine MTCs were not cured. One patient died after 9 years of follow-up at 21 years old (M918T RET+).ConclusionsFrom these data, it is clear to see the importance of genetic counseling and RET screening in all first-degree relatives of patients with proven MEN2. The goal should be to subject patients to surgery for prophylactic and not curative purposes, i.e., before the onset of MTC, given the high risk of persistent or recurrent disease also in pediatric/adolescent patients.